UPAYA BARTENDER DALAM MENINGKATKAN KUALITAS PELAYANAN PADA THE SUNKEN POOL BARDI HOTEL BLUE-ZEA RESORT BY DOUBLE-SIX SEMINYAK BALI - Ni Nyoman, Rusmiati; Suryadatana, I Made Riyan; Sulastri, Ida Ayu Putu (Universitas Triatma Mulya, 2022)
Hotel Blue-Zea is a four-star hotel located on Jalan Camplung Tanduk, Seminyak, which was established in 2019. The purpose of this study was to determine the bartender's efforts to improve service quality at the sunken pool bar at the Blue-Zea Hotel resort by double-six Seminyak Bali. The researcher uses a qualitative descriptive method by paying attention to the quality of service and the problems discussed, the qualitative descriptive method is the answer that is re-described by the author to answer the existing questions. The results of this study are that in improving the quality of service at the Sunken Pool Bar at the Blue-Zea Resort By Double-Six Seminyak Bali, there are several obstacles faced such as there are still some bartenders who do not follow the standard receipe prepared by management and there are bartenders who do not apply FIFO (first in first out) method.